Recovery of Manganese from Manganese Ore Reductive Acid Leaching Process Using Reeds (Imperata Cylindrica) as Reducing Agent - Suhaimi, Lalu; Bahtiar, Samsul; Sarina, Andi; Khairunnisya, Khairunnisya (National Research and Innovation Agency (BRIN), 2023)
Recovery of manganese from manganese ores was investigated by reductive leaching method using reeds as a reductant in the sulfuric acid medium. Cellulose, hemicellulose, and lignin are natural reducing agents which are widely used as reducing agents to recover manganese. Effects of calcination temperature and the holding time calcination on the leaching efficiency of manganese and impurities were examined. The calcination temperature and the holding time calcination have a significant effect on the extraction of manganese. The experimental results demonstrated that the higher the calcination temperature used, the higher the percentage of manganese obtained, namely 79.58% and 87.38%, respectively. The XRD (x-ray diffraction) pattern shows that the manganese phases formed at 700 and 800 °C are Mn3O4 (hausmannite) and Mn2O3 (bixbite), respectively. The morphology in the sample with calcination temperature at 700 °C showed agglomerate- shaped particles and unevenly dispersed. Meanwhile, the sample with calcination temperature at 800 °C exhibited agglomerated particles of inhomogeneous size and were more evenly distributed. Variation of holding time in the manganese ores recovery process also affects the results of manganese recovery. The composition of the manganese recovery in the samples using holding time calcination variations of 3 and 4 hours was 83.88% and 89.24%, respectively. The results of the XRD analysis showed that the manganese phase formed using 3 hours of calcination holding time was dominated by Mn3O4 (hausmannite). Meanwhile, the manganese phase formed using 4 hours of holding time of calcination was dominated by Mn2O3 (bixbite).